Adaptation and Psychometric Testing of the Czech and Slovak Version of the Missed Nursing Care in Infection Prevention and Control Survey - Gurková, Elena; Blackman, Ian; Bartoníčková, Daniela; Jarošová, Darja; Machálková, Lenka; Šáteková, Lenka (Journal of nursing measurement, 2022)
BACKGROUND AND PURPOSE: Only a limited number of items involved in missed nursing care inventories specifically focused on infection control practices. The study aimed to adapt and evaluate psychometric properties of the Czech and Slovak version of the Infection Control Missed Care survey; and to assess and compare the amount, type,and reasons for missed nursing care in infection prevention and control amongCzech and Slovak nurses. METHODS: The convenience sample of 1459 nurses from the Czechand Slovak republic was recruited. Analysis of the nurses' responses to both subscales of the surveys and validation of their data was undertaken using the item response theory (Rasch scaling). RESULTS: The now-modified Czech version consists only of 20 items measuring the type and frequency of missed care and 11 items focusing on the reasons for missed care. The now modified Slovak version consists of 34 items measuring the type and frequency of missed care and 17 items measuring the reasons for missed care. Reliability estimates with the removal of unreliable items showed acceptable reliability estimates for both sub-scales of the instrument. CONCLUSIONS: With modification to the two subscales used in the survey (removal of poorly fitting items) it should be reliable, and the resulting data could be used for further investigation such as factor analysis or modelling. The modified Infection Control Missed Care survey could be useful in further research investigating a relationship between nurse staffing, skill mix, and infection control outcomes in acute care hospitals.
Keywords: Slovenská republika; reprodukovatelnost výsledků; průzkumy a dotazníky; Surveys and Questionnaires; rasch analysis; healthcare-associated infections; Humans; missed nursing care; Česká republika; lidé; psychometrie; Reproducibility of Results; infection prevention and control; Psychometrics; Czech Republic; Slovakia